PENGARUH REGULASI BIAYA NIKAH DAN TRANSPARANSI TERHADAP TINGKAT KEPUASAN MASYARAKAT PADA PELAYANAN PERNIKAHAN DI KUA KECAMATAN BAJENG BARAT KABUPATEN GOWA - Muhammad Fauzan; Hasyim Halim; Karmila Karmila (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to examine the influence of Marriage Cost Regulation and Transparency on the Level of Public Satisfaction with marriage services at the Office of Religious Affairs (KUA) in Bajeng Barat Subdistrict, Gowa Regency. The method used is a quantitative approach with multiple linear regression analysis techniques. The research sample involved 96 community members selected using the Lemeshow method. The partial test results indicate that Marriage Cost Regulation (X1) does not have a positive effect on the Level of Public Satisfaction (Y) with marriage services, with a significance value of 0.428 > 0.05 and a t-count of -0.797 < t-table value of 7.201. This indicates that the regulation of marriage costs at the KUA is already perceived as a standard procedure that is ‘simply enforced,’ and thus, it does not become a main concern for the community in evaluating the service. Furthermore, the partial test results show that Transparency (X2) has a positive and significant effect on the Level of Public Satisfaction (Y), with a significance value of 0.028 < 0.05 and a t-count of 2.238 < t-table value of 7.201. This means that when the community is provided with open and honest information, they feel involved and treated fairly. The F-test results indicate a significance value of 0.001 < 0.05 and an F-count of 2.538 < F-table value of 3.100, which leads to the conclusion that Marriage Cost Regulation and Transparency simultaneously have no significant effect on the Level of Public Satisfaction with marriage services at the KUA in Bajeng Barat Subdistrict, Gowa Regency.